2022
DOI: 10.1177/08862605221140035
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Autonomy in Appalachia: An Investigation into Perceived Contraceptive Pressure

Abstract: The reproductive autonomy of persons who can give birth can be impeded through forms of interpersonal violence and coercion. Moreover, macro-level factors (e.g., poverty, discrimination, community violence, legislative policies) may impede the reproductive autonomy of entire communities. This study investigates a form of violence we term perceived contraceptive pressure in Appalachia, an understudied region of the Eastern U.S., regarding reproductive health and decision-making. Through targeted Meta advertisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(79 reference statements)
0
4
1
Order By: Relevance
“…More than one in three participants reported ever experiencing some contraceptive coercion. This frequency is slightly lower than that reported by Huslage et al 27 who found that half of Appalachians in the same sample reported perceptions of contraceptive coercion, because the previous study included an additional measure of sterilization pressure, and examined pressure from others, including partners and family members, in addition to pressure from health care providers.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…More than one in three participants reported ever experiencing some contraceptive coercion. This frequency is slightly lower than that reported by Huslage et al 27 who found that half of Appalachians in the same sample reported perceptions of contraceptive coercion, because the previous study included an additional measure of sterilization pressure, and examined pressure from others, including partners and family members, in addition to pressure from health care providers.…”
Section: Discussioncontrasting
confidence: 58%
“…However, we know very little about the types and impacts of coercion in contraceptive counseling in the Appalachian region. In one of the only existing studies on this topic in Appalachia, approximately half of participants reported experiencing at least one form of contraceptive coercion 27 . This high rate of contraceptive coercion indicates a need for research exploring how these coercive practices manifest and how they may impact the health and autonomy of Appalachian patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 It consists of 14 items and 3 subscales. In the scale, the subdimensions of freedom from coercion (5)(6)(7)(8)(9) and the communication subdimension (10)(11)(12)(13)(14) comprised of five items, and the decision-making subscale consists of four items (1-4) is formed. The subscale of freedom from coercion is coded as a reverse item.…”
Section: Reproductive Autonomy Scalementioning
confidence: 99%
“…Obstacles against women's reproductive autonomy include hiding contraceptive methods, restricting women's access to family planning services, making holes in condoms, forcing women to get pregnant, and using violence. [6][7][8] These emerging situations cause severe consequences in women, such as unwanted pregnancy, abortion, sexually transmitted infection, adverse pregnancy outcomes, and psychological trauma, which endanger the health of the woman and the baby. 4,6,9,10 Consequently, reproductive autonomy is an issue that needs to be emphasized because it affects the health of both the woman and the baby.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation